Aplicación de sistema alternativo para la toma de lecturas en la Agencia Morelia Sur y su rentabilidad utilizando la metodología de la mejora continua - Reyes Rangel, Agustín (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
Companies that are at the forefront are those that apply methodology tip to make your processes, that is why the Federal Electricity Commission Area Agency Morelia south has taken up the challenge of implementing the certification of supplies through radio frequency, focused improve the care of their clients and the reduction of irregularities in a sector of the city of Morelia which presented a problem not having access to strong staff to measuring equipment. The system of Quality Management Center in the West Division of the Federal Electricity Commission allows us to use quality methodologies to consolidate our company with world-class connotations and a tool is the Continuous Improvement in which he serves as a framework for this work. In the process of Marketing at Low Voltage Agency Morelia south we found the resources to the task of divisional offices and at the request of the Management Agency to become the first pilot to break into a system of technological advancement through radio frequency meters and Itron with a system compatible with Genesis and with the SICOM able to take readings via radio frequency, catch them in a portable terminal and process them through the systems that we work with the agency with a high degree of reliability and efficiency. This thesis in her first chapter includes a research paper of the main theories of quality, well, as their precursors and their contributions as a theoretical framework. The second chapter describes the Methodology of Improvement of Deming continued with its different stages and objectives that apply to the implementation and monitoring of remote readings in the historic center of the city of Morelia. The third chapter shows the stages of implementation of remote readings based on the methodology of Deming; each stage makes the description of the problem we face developments, the implementation to achieve results.

Las empresas que van a la vanguardia son las que aplican Metodología de punta para realizar sus procesos; es por eso que la Comisión Federal de Electricidad Zona Morelia Agencia Morelia Sur ha tomado el reto de implementar la certificación de suministros por medio de radiofrecuencia, enfocado a mejorar la atención de sus clientes y la disminución de las inconformidades en un sector de la ciudad de Morelia que presentaba una problemática fuerte al no tener acceso el personal a los equipos de medición. El sistema de Administración de la Calidad en la División Centro Occidente de la Comisión Federal de Electricidad nos permite utilizar metodologías de calidad encaminadas a consolidar nuestra empresa con connotaciones de clase mundial y una herramienta es la Mejora Continua en la cual sirve como marco para el presente trabajo. En el proceso de Comercialización en Baja Tensión de la Agencia Morelia sur nos dimos a la tarea con recursos de oficinas divisionales y a petición de la gerencia de convertirnos en la primer Agencia piloto para incursionar en un sistema de avance tecnológico por medio de radiofrecuencia y medidores Itron con un sistema compatible con el Génesis y con el sicom poder tomar lecturas por medio de radiofrecuencia , capturarlas en una Terminal portátil y procesarlas por medio de los sistemas que trabajamos en la Agencia con un alto grado de confiabilidad y eficiencia. Esta tesis comprende en el primer capítulo una investigación documental de las principales teorías de la calidad, así; como sus precursores y sus aportaciones como marco teórico. El segundo capítulo describe la Metodología de la Mejora continua de Deming con sus diferentes etapas y objetivos que se aplican a la implementación y seguimiento de las lecturas remotas en el centro histórico de la Ciudad de Morelia.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2008-0116; Calidad; Lecturas; Agencia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5906